Traditional Rice-Fish Farming of Mao Indigenous Community, Manipur, India - Abujam, Santoshkumar; Soram, Jiten Singh; Singh, Laishram Shantikumar; Sarma, Jyotishmita; Bhowmik, Debashree (International Journal of Ecology and Environmental Sciences, 2024)
The present investigation was carried out in terrace rice field of Mao Sub-division of Senapati district, Manipur, north-east India. The native indigenous community, Mao Naga, mainly practiced two types of agricultural practices viz., shifting cultivation and terrace cultivation. The physico-chemical parameters of the rice field are: average atmospheric temperature 21oC; water temperature 18.5oC; pH 7.9; conductivity 143.79 µmho/cm; dissolved oxygen 8.22 mg/l; FCO2 11.5 mg/l; alkalinity 123.07 mg/l; phosphate 0.362 mg/l and nitrate 0.07 mg/l. Indigenous carps such as Labeo rohita, L. bata, L. catla and fish such as Channa punctata and C. striatus were cultured in both perennial and seasonal rice fields with the local rice varieties such as Phurel, Phicharo, Muzharo, Mikhriro, Chusoro, Rodziiro, Romonoro and Disha. The rice variety Mikhriro is the costliest and famous for its flavour and stickiness. One ha of rice-fish culture field produced 3,500 kg of paddy (Rs. 52,500/-) and 200 kg of fish (Rs. 30,000/-) in one year. The net profit for perennial rice-fish field was Rs. 54,200/ha (against expenditure Rs. 28,300/ha) and Rs. 43,700/ha for the seasonal field (against expenditure Rs. 38,800/ha).